DEVELOPMENT OF THE SHARIA CAPITAL MARKET IN INVESTMENTS BASED ON SHARIA PRINCIPLES - Edy Setyo Wibowo (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The Sharia capital market is here to provide opportunities for Muslims and non-Muslims who want to invest their funds in accordance with Sharia principles which provide peace of mind and halal confidence. The Islamic capital market also acts as a global bridge to strengthen economic relations between countries and diversify investment portfolios. The integration of sharia principles in global finance is a pillar of sustainable economic development. By continuing to encourage innovation, adequate regulations and public awareness, the Islamic capital market has the potential to develop and make a significant contribution to the global economy. Investment based on Sharia principles is the main driver of promising Sharia economic growth, especially in key developing sectors. Significant developments have been seen in the Islamic banking sector, which not only provides an alternative to customers who wish to avoid interest, but also provides financial solutions that comply with Islamic principles of ethics and justice. The development of the Islamic capital market shows great potential for sustainable economic growth. Although challenges remain, concrete steps in increasing regulatory clarity, supporting product innovation, and increasing public awareness can help strengthen Islamic capital markets at the global level.